Model Pembelajaran Pendidikan Agama Islam Berbasis Multimedia Dalam Memotivasi Belajar Siswa Kelas VIIA Di SMP Negeri 1 Sawit Seberang - Tanjung, Ellisa Fitri; Manalu, Hani Zahra Br B. (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
Multimedia in the teaching and learning process aims to help educators explain difficult material. The use of multimedia technology can raise motivation to learn and make learning more interesting. Multimedia technology is very efficient in terms of time for educators because without having to ask students to record the material, they simply copy the file of the material that has been delivered. The aim of this research is to identify Islamic Religious Education learning in instilling student motivation to learn in class VIIA at SMP Negeri 1 Sawit Seberang. The results of the research show that Islamic Religious Education Learning uses a multimedia model, namely using several learning media (multimedia) which is very influential.